Revisiting established medicines: An overview of systematic reviews about ibuprofen and paracetamol for treating pain in children. (18th March 2019) - Radman, Marija; Babic, Andrija; Runjic, Edita; Jelicic Kadic, Antonia; Jeric, Milka; Moja, Lorenzo; Puljak, Livia
Abstract: Background and objective: We explored how systematic reviews evaluated paracetamol and ibuprofen for treating pain in children, as these two non‐opioid analgesics are well‐established medicines included in most national essential medicines lists. Databases and data treatment: We carried out an overview of systematic reviews (SRs) of randomized controlled trials (RCTs) of interventions (PROSPERO registration: 42016045367). We searched MEDLINE, EMBASE, Cochrane Database of Systematic Reviews (CDSR) and Database of Reviews of Effects (DARE) up to 23 August 2017. We used AMSTAR checklist to analyse methodological quality of included SRs. Results: We found 17 SRs with 72 unique RCTs; the majority of those trials included under 100 children. Positive conclusive evidence was found in only one SR, regarding safety of paracetamol. Conclusions of other SRs for efficacy and safety of ibuprofen and paracetamol were inconclusive, unclear, or there was no opinion. Only one SR analysed efficacy of ibuprofen and other non‐steroidal anti‐inflammatory drugs (NSAIDs) in chronic pain and the conclusion was that there was no evidence from RCTs that NSAIDs were effective for chronic non‐cancer pain in children and adolescents. Most of the SRs addressed very narrow questions, included few trials, with few children and were of low or medium methodological quality. Conclusions: Most SRs on two relevant medicines have inconsistent conclusions and doubt upon their effectiveness. Instead of focusing on very narrow questions, SRs should examine more comprehensive research topics to obtain a general sense of consistency, particularly when analysing established medicines. Significance: Evidence behind two analgesics—ibuprofen and paracetamol—that are well‐established medicines for children in most countries appears limited, judging by the systematic reviews. The discrepancy between clinical use and the extensive evidence we reviewed may be a result of the selective criteria in the reviews examined. We need new, and better evidence syntheses supporting the use of these two medicines in wide indications regarding pain in children.